2008
DOI: 10.1038/onc.2008.324
|View full text |Cite
|
Sign up to set email alerts
|

p53 controls hPar1 function and expression

Abstract: Human protease-activated receptor 1 (hPar1) is a bona fide receptor of the hemostatic protease thrombin, and has a central function in tumor progression. Inactivation of the tumor suppressor gene p53 is one of the most common genomic alterations occurring in cancer. Here, we address the interrelations between p53 and hPar1 in cancer. We demonstrate an inverse correlation between hPar1 gene expression and wild-type (wt) p53 levels, and a direct correlation with levels of the mutant (mt) p53. Bioinformatic searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…These data demonstrate the specific inhibitory effect of p53WT on TFF2 promoter activity. Moreover, p53R175H upregulated the expression of c-Fos in Kato-III cells, consistent with previous report that p53R175H increased the expression of c-Fos in p53-null H1299 cells (39) (Fig. 3F).…”
Section: Resultssupporting
confidence: 92%
“…These data demonstrate the specific inhibitory effect of p53WT on TFF2 promoter activity. Moreover, p53R175H upregulated the expression of c-Fos in Kato-III cells, consistent with previous report that p53R175H increased the expression of c-Fos in p53-null H1299 cells (39) (Fig. 3F).…”
Section: Resultssupporting
confidence: 92%
“…However, studies from the cancer literature show that the PAR1 promoter is regulated by p53, the androgen receptor, and activator protein 2 (AP2). [88][89][90] Although PAR expression has not been directly connected to epigenetic factors, recent studies have correlated hypomethylation of f2rl3 (the PAR4 gene) to smoking in multiple populations. [91][92][93][94] The decreased methylation of f2rl3 is linked to an increase in mortality due to coronary heart disease when other factors are controlled and is a potential biomarker.…”
Section: Regulation Of Par Expression and Polymorphismsmentioning
confidence: 99%
“…Previous studies showed that these transactivation domain residues may interact with a number of proteins including Mdm2, adenovirus E1B 29, TAFs 30 and p300 31. In addition, p53-V173L, p53-R175H and p53-H179Q are commonly found in human cancers 32. Moreover, several p53 hotspot mutations (R175H, R248W and R273H) were found not only lost p53-dependent tumor suppressor activities, but also acquired new oncogenic activities to promote progression of cancers 33.…”
Section: Discussionmentioning
confidence: 99%